Information Technology and Productivity Growth in Asia - Lee, Il (IMF Working Papers; Working Paper, 2003)
The contribution of the information and communication technology (ICT) sector to growth in Asian economies is clearly evident from the expenditure side (net exports) and became particularly significant in the second half of the 1990s. This paper employs an extension of the standard growth accounting framework, using estimates of stock of ICT capital (hardware, software, and telecommunications equipment), to estimate the direct contributions to growth. The contribution of ICT to growth in Asia during the 1990s is found to be mainly from capital deepening. Total factor productivity (TFP) is also decomposed (using the dual-or revenue-based-approach) into the contributions of non-ICT capital stock, ICT capital stock, and labor. TFP growth is found to be relatively small in most Asian countries.